Influence of Leadership Style and Teamwork on Employee Work Motivation at Rumah Zakat Center, Bandung City - Sitepu, Siti Karolina; Haris, Ibnu; 0, Taryono (Universitas KH. Abdul Chalim Mojokerto, 2025)
The purpose of this research is to examine the impact of leadership style and teamwork on employee work motivation at Rumah Zakat Pusat Kota Bandung. The research subjects consisted of all active employees at Rumah Zakat Pusat Kota Bandung, with a total population of 152 people. From the total population, some were taken as research samples with a convenience sampling pattern, resulting in 60 respondents. The tool used in the study was a questionnaire containing statements that had been tested for data validity and reliability, to ensure that the data used was accurate. Data analysis was carried out using multiple linear regression, F test, and T test through SPSS 26 to evaluate the relationship between the variables studied. The results showed that leadership style and teamwork simultaneously had a positive and significant effect on employee work motivation at Rumah Zakat Pusat Kota Bandung. With an adjusted R-squared of 51%, it can be concluded that these two independent variables contributed 51% to increasing employee work motivation, while the rest was influenced by other factors that were not part of this study.